2022
DOI: 10.3390/life12081223
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after Prenatal Diagnosis of Trisomy 13, 18, and 21 in Fetuses with Congenital Heart Disease

Abstract: Fetal congenital heart disease (CHD) is often associated with chromosomal abnormalities. Our primary aim was to assess stillbirth and neonatal mortality rates for pregnancies complicated by trisomies 13, 18, and 21 in the presence of CHD, from a single tertiary referral center during 2000–2020 in a retrospective cohort study. The secondary aims were to investigate maternal morbidity in these pregnancies, and to study the gestational or neonatal age when mortality occurred. Inclusion criteria were the prenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…In the cases of IUFD, these events occurred only in the third trimester but all between 30 and 35 weeks of gestation, which was also reported in previous studies 13,19 . Previous studies reported IUFD in 10%–12% of ongoing pregnancies in trisomy 21 fetuses 33,34 . This is similar to the rates observed in our prenatal cohort with IUFD in 13.3% (2/15) of the ongoing pregnancies with trisomy 21.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the cases of IUFD, these events occurred only in the third trimester but all between 30 and 35 weeks of gestation, which was also reported in previous studies 13,19 . Previous studies reported IUFD in 10%–12% of ongoing pregnancies in trisomy 21 fetuses 33,34 . This is similar to the rates observed in our prenatal cohort with IUFD in 13.3% (2/15) of the ongoing pregnancies with trisomy 21.…”
Section: Discussionsupporting
confidence: 90%
“…13,19 Previous studies reported IUFD in 10%-12% of ongoing pregnancies in trisomy 21 fetuses. 33,34 This is similar to the rates observed in our prenatal cohort with IUFD in 13.3% (2/15) of the ongoing pregnancies with trisomy 21. This finding emphasizes the possible association between trisomy 21 and stillbirth.…”
Section: Discussionsupporting
confidence: 88%
“…2 These data have remained consistent since the introduction of noninvasive prenatal screening. [3][4][5][6][7] However, data on the incidence of abortions performed for fetal indication in the United States are limited, because this information is not collected at the state or national level.…”
mentioning
confidence: 99%